Youth employment interventions – main challenges - Jelonek, Magdalena (Journal of Public Governance, 2018)
The purpose of this paper is a critical analysis of the assumptions underlying STW (school to work) public interventions aimed at improving employment opportunities and transition of graduates from education to the labour market. Particular attention has been devoted to one Polish initiative named Youth Guarantee. The text assumes that the effectiveness of such interventions depends on several external factors: on the macro (i.e. the condition of the economy, the demographic situation) and the micro level (i.e. factors differentiating individual decisions). The author identifies key challenges facing those implementing Youth Guarantee initiative.